Development and optimization of a method for determining betaine and trigonelline in the fruits of Lycium species by using solid‐phase extraction combined with high‐performance liquid chromatography–diode array detector. Issue 11 (29th March 2020) - Liu, Wenjing; Xia, Mengqin; Yang, Li; Wang, Zhengtao; Wang, Rui; Shi, Yanhong
Abstract: Betaine is an essential nutrient for humans and a source of methyl donors for methionine and S ‐adenosylmethionine formation, and it is used as a biomarker for pharmacological activities and to evaluate the quality of Lycium species and common foods. However, because of its special structural features, poor ultraviolet‐chromophore, and high polarity, the existing methods for betaine extraction and quantification cannot provide higher extraction efficiency, better sensitivity, or resolution degree. A simple, fast, and efficient high‐performance liquid chromatography–diode array detector coupled with solid‐phase extraction was adopted for simultaneous separation and quantification of betaine in four types of Lycium species. The results revealed that after degreasing with dichloromethane, extraction with 80% ethanol (pH adjusted to 1.0 with hydrochloric acid), and elution with aluminum oxide (OH − form), the improvement in the average yield rate of betaine was thrice of that of the existing methods. In addition, trigonelline was identified as the interfering substance of betaine for the first time in Lycium species, and betaine and trigonelline were simultaneously separated and quantified. Furthermore, their chemical characteristics and content distribution in different Lycium species were carried out.